Perancangan Manajemen Risiko Operasional Sistem Pemerintahan Berbasis Elektronik - Putri, Vany Adelia; Pradnyana, I Made Ardwi; Indradewi, I Gusti Ayu Agung Diatri (Maranatha University Press, 2025)
Risk management in Information Technology (IT) is a crucial element for every organization, including government institutions. Currently, the Department of Communication, Informatics, Encryption, and Statistics of Buleleng Regency (Diskominfosanti Kab. Buleleng) does not have a specific approach to systematically managing IT risks. The Electronic-Based Government System (SPBE) is a government initiative that optimizes the use of IT and communication to provide services to the public. Implementing risk management in SPBE presents an opportunity for government agencies to enhance operational efficiency and drive innovation. This study aims to develop an initial guideline for SPBE risk management at Diskominfosanti Kab. Buleleng, with the goal of improving the institution’s SPBE index. The guideline design refers to the provisions outlined in Presidential Regulation (Perpres) No. 95 of 2018 and Ministerial Regulation of PANRB No. 5 of 2020 concerning SPBE Risk Management Guidelines. The approach used in this guideline integrates the COBIT 5 for Risk framework to identify, analyze, and evaluate various potential risks. The research findings identify 30 risks, consisting of 2 positive risks and 28 negative risks. The risk mitigation strategy design covers aspects of human resources, technology, and operational processes. This study produces three key outputs: risk identification, risk assessment, and a risk mitigation strategy framework for SPBE services implemented at Diskominfosanti Buleleng.